Calcium Phosphate Loaded with Curcumin Prodrug and Selenium Is Bifunctional in Osteosarcoma Treatments - Mingjie Wang; Chunfeng Xu; Dong Xu; Chang Du; Yuelian Liu (Journal of Functional Biomaterials)
Although SeO32− ions have been loaded onto calcium phosphate to treat a wide range of cancers, the quest to promote bone tissue regeneration is still ongoing. Curcumin (cur), an herbal extraction, can selectively inhibit tumor cells and promote osteogenesis. In this study, SeO32− ions were co-precipitated in biomimetic calcium phosphate (Se@BioCaP), and modified curcumin prodrug (mcur) was adsorbed on diverse Se@BioCaP surfaces (mcur-Se@BioCaP-Ads). Co-precipitation yielded Se@BioCaP with a significantly higher Se content and exhibited a tailorable micro-/nanostructure. The favorable pH-responsive release of Se and mcur from mcur-Se@BioCaP-Ads showed a synergistic anticancer efficiency in OS cells, enhancing OS cell inhibition more than a single dose of them, which might be associated with ROS production in OS cells. In addition, increased alkaline phosphatase activity and calcium nodule formation in MC3T3-E1 pre-osteoblasts were also verified. These results suggest this novel mcur-Se@BioCaP-Ads has promising and widespread potential in OS treatments.